Pengaruh penambahan limbah teh dalam pakan terhadap penampilan produksi telur burung puyuh - Setyawan, Agus Erta; Sudjarwo, Edhy; Widodo, Eko; Prayogi, Heni Setyo (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2013)
The study aims at examining the effect of adding tea waste into the quail feed on the aspects of the quail production performances including feed consumption, daily egg production (Hen Day Production/HDP) and feed conversion. Materials on this study were 100 quails aged 7 months old with experimental period of 35 days. Tea waste used in this research was obtained from the tea industry of Wonosari (Lawang). The method was experiment, and the design was one-way completely randomized design. The treatments used in this study were level of adding tea waste of 0; 1.25; 2.5; 3.75; and 5.0% in feed. Every treatment was repeated 4 times and every replication used 5 quails. The study shows that tea waste addition in feed did not significantly influence (P>0.05) feed consumption, daily egg production (Hen Day Production/HDP, and feed conversion of quail. The study concludes that tea waste addition into the feed until level 5% did not influence feed consumption, HDP (Hen Day Production), and feed conversion of quail. It could be suggested to do further research involving the increasing level or by taking the topic of how to minimize the anti-nutrient effect (tannin) of tea waste. Keywords: quails, tea waste, production performance